STRATEGI GURU AKIDAH AKHLAK DALAM MENANAMKAN KARAKTER ISLAMI PESERTA DIDIK MTs. GUPPI SAMATA GOWA - Kalsum, Ummu (Inspiratif Pendidikan, 2018)
Abstract: The purpose of this research is to: (1) know the strategy of the teacher of Akidah Akhlak in instilling the Islamic character of the students of MTs Guppi Samata Gowa (2) to know the supporting factor of Akidah Akhlak teacher in instilling the Islamic character of MTs Guppi Samata Gowa students, (3) knowing the inhibiting factor teacher of morality in instilling the character of Islmi learners MTs Guppi Samat Gowa.This type of research is a qualitative descriptive research. Research location at MTs Guppi Samata Gowa. The sources of data in this study are primary data sources that include: Subject Guru Akidah Akhlak, principal MTs Guppi, teachers BK, and representatives of students MTs Guppi Samata Gowa. While the secondary data source is the documents associated with the object under study. Data collection methods used are observation, interview and documentation. The research approach used is paedagogic approach and psychological approach. Data processing techniques and data analysis used are (1) Data Reduction (Data Reduction) (2) Data Presentation (Data Display) (3) Withdrawal of Conclusions (Verivication / Conclusion Drawing).The results of this study are: (1) Teachers' Strategy Akidah Akhlak in inculcating Islamic character of MTs Guppi Samata Gowa students: giving advice and motivation, exemplary, habituation, delivery of learning by lecture method, assignment and punishment for learners who violate regulation or school order. (2) Factors supporting morality character in instilling Islamic character of students MTs Guppi samata Gowa consists of two factors, namely internal and external, internal factor is the cooperation between teachers in school and the extracurricular in MTs Guppi Samata Gowa, while the external factor positive response from government, cooperate with other institution and support parent. (3) Inhibiting factor of teachers of Akidah Akhlak in instilling Islamic character of MTs students. Gata Samata Gowa consists of internal factors and external factors, internal factors such as school security, facilities and infrastructure. And external factors that is cooperation with parents of learners, social environment of society and peers.While the implication in this research is strategy of Akidah Akhlak teacher in instilling Islamic character of MTs Guppi Samata Gowa students, it is considered effective and worthy to be maintained. And my advice needs to be done continuously in the learning process, but the teacher must always make innovation in setting the right strategy, in accordance with the title of material aqidah morals are taught, for the cultivation of Akhlak al-karimah learners able to develop optimally.